Getting beyond better how social entrepreneurship works - Martin, Roger L., author (Harvard Business Review Press, 2015)
"Who really moves things forward in our society and how do they do it? How have they always done it? Strategy guru Roger Martin and Skoll Foundation CEO Sally Osberg make a compelling argument that social entrepreneurs are agents of change who recognize, in our current reality, various kinds of "equilibria"-systems in need of change-and then advance social progress by transforming these systems, ultimately replacing what exists with a new equilibrium. Seen in this light, social entrepreneurship is not a marginal activity, but one that unleashes new value for society by releasing untapped human ambition. The book begins with a probing and useful theory of social entrepreneurship, moving through history to illuminate what it is, how it works, and the nature of its role in modern society. The authors then set out a framework for understanding how successful social entrepreneurs actually go about producing transformative change. There are four key stages: understanding the world; envisioning a better future; building a model for change; and scaling the solution. With both depth and nuance, Martin and Osberg offer rich examples and stories, and share lessons and tools applicable to everyone who aspires to drive positive change, whatever the context. Getting Beyond Better offers a bold new framework demonstrating how and why meaningful change actually happens in the world, and offering concrete lessons and a practical model for businesses, policy-makers, and civil society organizations to generate new value, again and again. "-- Provided by publisher